(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This research is a Classroom Action Research (CAR) consisting of two cycles aimed at improving forward roll ability through game-based learning methods in Grade IV students of SD Inpres 2 Kaluku Tinggu. This study involved 21 students with a total sampling technique. Data were obtained through game-based learning treatment and observation of forward roll ability in floor gymnastics. The data analysis technique used descriptive statistics with percentages. The results showed an increase in forward roll ability from cycle I to cycle II. In cycle I, the completion rate reached 66% and increased to 95% in cycle II. The average value also increased from 74 in cycle I to 82 in cycle II. These findings indicate that game-based learning methods are effective in improving forward roll ability in Grade IV students of SD Inpres 2 Kaluku Tinggu.